2009
DOI: 10.1038/nm.1946
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite allergen induces asthma via Toll-like receptor 4 triggering of airway structural cells

Abstract: Barrier epithelial cells and airway dendritic cells (DC) make up the first line of defence against inhaled substances like house dust mite (HDM) allergen and endotoxin. We hypothesized that these cells need to communicate to cause allergic disease. Using irradiated chimeric mice, we demonstrate that TLR4 expression on radioresistant lung structural cells is required and sufficient for DC activation in the lung and for priming of effector T helper responses to HDM. TLR4 triggering on structural cells caused pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
1,001
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,009 publications
(1,051 citation statements)
references
References 46 publications
38
1,001
3
9
Order By: Relevance
“…Less is known which PRRs drive Th2-cell associated immune responses. Recent reports suggest that house dust mite allergens initiate asthmatic inflammation by signaling through the TLR4 receptor complex in part by LPS contamination [45,46]. Our data show that the T. brucei antigen MiTat1.5 sVSG-conditioned DCs to produce IL-6 and IL-1b, which is dependent on TLR4 and the adaptor molecule MyD88.…”
Section: Discussionmentioning
confidence: 53%
“…Less is known which PRRs drive Th2-cell associated immune responses. Recent reports suggest that house dust mite allergens initiate asthmatic inflammation by signaling through the TLR4 receptor complex in part by LPS contamination [45,46]. Our data show that the T. brucei antigen MiTat1.5 sVSG-conditioned DCs to produce IL-6 and IL-1b, which is dependent on TLR4 and the adaptor molecule MyD88.…”
Section: Discussionmentioning
confidence: 53%
“…65 Interestingly, we found expression of IL-33R on eosinophils in this study of pulmonary cryptococcosis (data not shown). Thus, eosinophils could be cellular targets of IL-33 produced by epithelial cells 66 and, thereby, could contribute to Th2 initiation. The definitive roles of IL-33, its cellular sources, and targets in anticryptococcal immunity remain to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of the TLR4 ligand LPS leads to a dramatic increase in motility and antigen sampling behaviour. Strikingly, instruction for this pattern of motility requires TLR4 triggering of neighbouring epithelial cells and not on DC directly [5]. It has not been studied whether lung DC subsets would differentially require this epithelial instruction.…”
Section: Functional Specializations Of Lung DC Subsetsmentioning
confidence: 99%
“…Immediately below, the lamina propria contains CD11b hi cDC [3][4][5] that express the SIRPa molecule (a ligand of CD47), and the CX3CR1 fractalkine receptor [6,7]. The conducting airways also contain pDC, best identified by additional staining for Siglec-H, or bone-marrow stromal antigen-2 (BST2) [1,2,8,9].…”
Section: Introducing Lung DC Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation